Pengaruh Crossword Puzzle terhadap Gangguan Fungsi Kognitif pada Pasien Stroke Iskemik - Satriani, Satriani; Sofiani, Yani; Rayasari, Fitrian; Yuntiri, Ninik; Mulyatsih, Mg Enny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to apply crossword puzzles to cognitive impairment in patients with ischemic stroke. The method used was a Randomized Controlled Trial with a Quasy Experiment research design carried out at PON Hospital Jakarta. The research results showed that there was a greater and more significant increase in cognitive function scores with a larger effect size than the current results. Meanwhile, for the MMSE method, the results obtained from the Paired T-Test test obtained an effect size value of 6.91 (moderate) and it can be assumed that the application of MMSE improves the results of cognitive function positively. In conclusion, crossword puzzle intervention can improve cognitive outcomes Keywords: Crossword Puzzle, Cognitive, Ischemic Stroke